2010
DOI: 10.1016/j.dnarep.2009.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Werner syndrome protein in protection of genome integrity

Abstract: OverviewWerner syndrome protein (WRN) is one of a family of five human RecQ helicases implicated in the maintenance of genome stability. The conserved RecQ family also includes RecQ1, Bloom syndrome protein (BLM), RecQ4, and RecQ5 in humans (see additional reviews in this issue), as well as Sgs1 in Saccharomyces cerevisiae, Rqh1 in Schizosaccharomyces pombe, and homologs in Caenorhabditis elegans, Xenopus laevis, and Drosophila melanogaster [1]. Defects in three of the RecQ helicases, RecQ4, BLM, and WRN, caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
209
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(220 citation statements)
references
References 243 publications
(334 reference statements)
10
209
0
1
Order By: Relevance
“…For instance, a deletion in WRN is found to be associated with higher mortality. The WRN gene encodes a RecQ DNA helicase involved in DNA replication and repair, transcription, and telomere maintenance (Rossi et al ., 2010). Deleterious mutations in this gene give rise to the premature aging syndrome Werner, and genetic variation in WRN has previously been associated with longevity (Soerensen et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a deletion in WRN is found to be associated with higher mortality. The WRN gene encodes a RecQ DNA helicase involved in DNA replication and repair, transcription, and telomere maintenance (Rossi et al ., 2010). Deleterious mutations in this gene give rise to the premature aging syndrome Werner, and genetic variation in WRN has previously been associated with longevity (Soerensen et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…41 The simultaneous involvement of at least 3 genes with a role for double strand break repair in case of 8p deletion would make those cancers particularly prone to development of such an "amplifier phenotype." 65 Several studies have suggested that cancers with a high degree of genomic instability might respond better to adjuvant radiation therapy or chemotherapy than genetically stable cancers. 68,69 It will thus be interesting to see if breast cancers with 8p-loss might respond better to neoadjuvant chemotherapy as compared to those lacking this alteration.…”
Section: Discussionmentioning
confidence: 99%
“…WRN it is a key regulator of fragile site stability 64 and involved in 2 major DNA repair pathways, the base excision repair (BER) and double strand break repair (DSBR) pathway. 65 In addition, POLB (8p11) and NAIL2 (8p23) are also involved in DNA repair as a key element in BER, and WRN likely acts cooperatively with POLB via its helicase and exonuclease activity. 66 It can be assumed that all these 3 interacting genes will be co-deleted in many cancers with 8p deletions.…”
Section: Discussionmentioning
confidence: 99%
“…There are five human RecQ-like proteins (RECQL1, BLM, WRN, RECQL4 and RECQ5), each having 3' to 5' DNA helicase activity, but little sequence similarity outside the helicase motifs (2,3). Three of these helicases (BLM, WRN and Rothmund-Thomson) show genomic instability and cancer susceptibility; however, each also has distinctive features (4,5).…”
Section: Introductionmentioning
confidence: 99%